2020
DOI: 10.1021/acsami.0c03363
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Design of a Highly Stable Single-Ion Conducting Polymer Gel Electrolyte

Abstract: Single-ion conducting (SIC) polymer electrolytes with a high Li transference number (t Li + ) have shown the capability to enable enhanced battery performance and safety by avoiding liquid−electrolyte leakage and suppressing Li dendrite formation. However, issues of insufficient ionic conductivity, low electrochemical stability, and poor polymer/electrode interfacial contact have greatly hindered their commercial use. Here, a Li-containing boroncentered fluorinated SIC polymer gel electrolyte (LiBFSIE) was rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(75 citation statements)
references
References 67 publications
0
75
0
Order By: Relevance
“…fabricated a lithium‐containing boron‐center fluorinated single‐ion conductive polymer gel electrolyte (LiBFSIE) (Figure 2h) by in situ method (Figure 4e), with a Li + transference number of 0.93 and an ionic conductivity of 2 × 10 −4 S cm −1 at 35 °C. [ 65 ] The average Coulombic efficiency of LiBFSI‐based cells reached 99.95% after 200 cycles, which was higher than that of LE based cells, with no significant capacity decay observed (Figure 4f). These benefits may be derived from in situ UV‐induced polymerization methods, which can optimize the interface contact.…”
Section: Organoboron Covalently Linked To Pesmentioning
confidence: 98%
“…fabricated a lithium‐containing boron‐center fluorinated single‐ion conductive polymer gel electrolyte (LiBFSIE) (Figure 2h) by in situ method (Figure 4e), with a Li + transference number of 0.93 and an ionic conductivity of 2 × 10 −4 S cm −1 at 35 °C. [ 65 ] The average Coulombic efficiency of LiBFSI‐based cells reached 99.95% after 200 cycles, which was higher than that of LE based cells, with no significant capacity decay observed (Figure 4f). These benefits may be derived from in situ UV‐induced polymerization methods, which can optimize the interface contact.…”
Section: Organoboron Covalently Linked To Pesmentioning
confidence: 98%
“…So far, extensive computational studies have been carried out to examine the structure‐ionic conductivity/transference number‐electrochemical performance relationships in SICPEs. [ 126–136 ] For example, McCloskey and co‐workers demonstrated that increasing the t Li + of the electrolyte could enable high power densities and fast charging of the cells. [ 62 ] Besides, the polymer electrolyte with high t Li + s could potentially suppress the concentration gradients and minimize the Li dendrite growth.…”
Section: Electrochemical Performance Of Sicpes For Li–metal Batteriesmentioning
confidence: 99%
“…Secondly, the kinetics of the electrochemical reaction is also affected by the dissociation of lithium ions in the electrolyte . Because the ionic radius of the lithium ion is small, coulombic interactions between the solvent molecules and lithium ions are strong and the activation energy for ion dissociation is high (about 50 kJ mol −1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the kinetics of the electrochemical reaction is also affected by the dissociation of lithium ions in the electrolyte. [364] Because the ionic radius of the lithium ion is small, coulombic interactions between the solvent molecules and lithium ions are strong and the activation energy for ion dissociation is high (about 50 kJ mol À 1 ). Surface functionalisation of the active materials (such as lithium manganese oxide and cobalt oxide) with functional groups enriched with electrons is recommended in order to decrease the energy barrier by enhancing the attractive interaction between lithium ions and active materials.…”
Section: Discussionmentioning
confidence: 99%